Oxidative stress: fundamentals and advances in quantification techniques - Krishnamurthy, Hari Krishnan; Pereira, Michelle; Rajavelu, Imbaasree; Jayaraman, Vasanth; Krishna, Karthik; Wang, Tianhao; Bei, Kang; Rajasekaran, John J. (Frontiers in Chemistry, 2024)
Oxidative species, generated endogenously via metabolism or from exogenous sources, play crucial roles in the body. At low levels, these species support immune functions by participating in phagocytosis. They also aid in cellular signaling and contribute to vasomodulation. However, when the levels of oxidative species exceed the body’s antioxidant capacity to neutralize them, oxidative stress occurs. This stress can damage cellular macromolecules such as lipids, DNA, RNA, and proteins, driving the pathogenesis of diseases and aging through the progressive deterioration of physiological functions and cellular structures. Therefore, the body’s ability to manage oxidative stress and maintain it at optimal levels is essential for overall health. Understanding the fundamentals of oxidative stress, along with its reliable quantification, can enable consistency and comparability in clinical practice across various diseases. While direct quantification of oxidant species in the body would be ideal for assessing oxidative stress, it is not feasible due to their high reactivity, short half-life, and the challenges of quantification using conventional techniques. Alternatively, quantifying lipid peroxidation, damage products of nucleic acids and proteins, as well as endogenous and exogenous antioxidants, serves as appropriate markers for indicating the degree of oxidative stress in the body. Along with the conventional oxidative stress markers, this review also discusses the role of novel markers, focusing on their biological samples and detection techniques. Effective quantification of oxidative stress may enhance the understanding of this phenomenon, aiding in the maintenance of cellular integrity, prevention of age-associated diseases, and promotion of longevity.